Are green offices better than conventional? - Zaid, S.M.; Kiani Rad, A.; Zainon, N. (Emerald, 2017)
Purpose: Global warming and climate change is one of the biggest issues facing humanity in this century; its effects are felt on the highest peaks of Mount Everest to the low-lying islands in the India Ocean. This century marked the highest amount of carbon dioxide (CO2) emitted, breaking records of the past 650,000 years, and we have pushed the climate to “a point of no return”. Much of the climate contribution has been linked to humanity’s thirst for higher living standards and lifestyle, which has led to higher consumerism, depletion of earth’s resources, production of massive waste and carbon emissions. Fast forward from the sustainability agenda of Brundtland set in 1987 and the increasing demand for energy consumption to cater for the current global inhabitants, many “green” efforts have been taken by the building industry to reduce the overall environmental impact. This purpose of this study is to compare energy performance of a conventional office building with a green certified building. Design/methodology/approach: This paper tries to bridge the performance gap by comparing measured operational energy consumption and carbon emission of Green Building Index (GBI)-certified office buildings in Kuala Lumpur, to determine whether “green buildings” are performing as intended in reducing their environmental impact. Findings: This paper highlighted and compared operational energy consumption and carbon emissions of a GBI-certified office with a conventional office building in Malaysia. The paper also discusses the performance gap issue and its common causes, and aims to compare predicted energy and operational energy performance of buildings. Originality/value: Initiatives such as “green” or “sustainable” design have been at the forefront of architecture, while green assessment tools have been used to predict the energy performance of a building during its operational phase. There is still a significant performance gap between predicted or simulated energy measurements to actual operational energy consumption. The need to measure actual performance of these so-called “green buildings” is important to investigate if there is a performance gap and whether these buildings can perform better than conventional buildings. Understanding why the performance gap occurs is a step in reducing actual and predicted energy performance in buildings.